The Effect of Green Product, Green Price, and Distribution Channel on The Intention to Repurchasing Simple Face Wash - Ella Anastasya Sinambela; Elok Imroatul Azizah; Arif Rachman Putra (Forum Kerjasama Pendidikan Tinggi, 2022)
Currently consumers have a high concern for the environment. This concern has an impact on products that consumers use in everyday life such as skincare. Simple is a skincare brand from England that has been in production since 1960. Simple has always stated that its products are environmentally friendly products. The competition that occurs in similar businesses makes Simple implement its marketing strategy for data to increase the intention to repurchase Simple skincare products. This study aims to determine the effect of green product, green price, and distribution channel on the intention to repurchase Simple face wash soap. The population of this quantitative research is the consumers of Simple face wash soap. Researchers used 100 respondents. The research data was then processed using multiple linear regression analysis techniques. The results showed that green products have a significant effect on the formation of repurchase intentions. Furthermore, the green price has also been shown to have a significant effect on the formation of repurchase intentions. The results also show that the formation of repurchase intentions is also influenced by the distribution channel.